2003
DOI: 10.1007/s00027-003-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CDOM in an organic-rich river and surrounding coastal ocean in the South Atlantic Bight

Abstract: Variability in chromophoric dissolved organic carbon (CDOM) was characterized in and around the Cape Fear River and Onslow Bay, North Carolina USA. The river end member of the study is extremely rich in CDOM, thus the Cape Fear River serves as a point source of CDOM-rich water into the southeastern Atlantic bight. The river plume is easily traceable and generally extends in a southwesterly direction along the coastline into Long Bay. Depending on physical processes and river flow, the plume can meander somewha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(113 citation statements)
references
References 55 publications
10
97
0
6
Order By: Relevance
“…7;Jaffe´et al, 2004). The inflection point appears when the concentration of terrestrial-derived DOM becomes c 147 comparable to marine-derived DOM (e.g., de Souza Sierra et al, 1997;Kowalczuk et al, 2003). In this study such 'blue shifts' were mostly observed for the water samples collected during the dry season when the loading of terrestrial DOM was lower.…”
Section: Ten Thousand Islands and Whitewater Baymentioning
confidence: 45%
See 2 more Smart Citations
“…7;Jaffe´et al, 2004). The inflection point appears when the concentration of terrestrial-derived DOM becomes c 147 comparable to marine-derived DOM (e.g., de Souza Sierra et al, 1997;Kowalczuk et al, 2003). In this study such 'blue shifts' were mostly observed for the water samples collected during the dry season when the loading of terrestrial DOM was lower.…”
Section: Ten Thousand Islands and Whitewater Baymentioning
confidence: 45%
“…The inflection point depends on the DOC concentration of freshwater and marine water, and in open coastal systems, blue shift of k max is usually observed at salinity higher than 30 ( Fig. 7; also see de Souza Sierra et al, 1997;Kowalczuk et al, 2003;Jaffe´et al 2004). The blue shift in lower salinity indicates FB contains a high concentration of DOC with marine origin.…”
Section: Florida Baymentioning
confidence: 86%
See 1 more Smart Citation
“…The C4 peak corresponds to a humic fluorophore freshly produced in the marine environment by microbial metabolism (Parlanti et al 2000; henceforth identified as Marine Humic-like). Components 1, 2 and 5 are similar to the fluorescence spectra of pure Tryptophan (C1) and Tyrosine (C2 and C5) (Coble 1996;Kowalczuk et al 2003). These three components represent a labile, bioavailable DOM fraction (Hudson et al 2007).…”
Section: Accepted M Manuscriptmentioning
confidence: 88%
“…to dark tea-colored (P. illinoensis). This coloration implies that these leachates are optically different and that, as a result, they could have different degrees of reactivity (Kowalczuk et al 2003, Boyd & Osburn 2004, Coble 2007. P. illinoensis is characterized by long stems that have fewer leaves than other submerged vegetation.…”
Section: Oc Utilization and Bioavailabilitymentioning
confidence: 99%